Altered Experiential, But Not Hypothetical, Delay Discounting in Schizophrenia - Horan, William P. (J Abnorm Psychol, 2017)
Delay discounting (DD) is a future-oriented decision making process that refers to whether one is willing to forego a smaller, sooner reward for the sake of a larger, later reward. It can be assessed using hypothetical tasks, which involve choices between hypothetical rewards of varying amounts over delay periods of days to years, or experiential tasks, which involve receiving actual rewards in real time over delay periods of seconds to minutes. Initial studies in schizophrenia have only used hypothetical tasks and have been mixed in finding either elevated or normal levels of DD. 131 outpatients with schizophrenia and 70 healthy controls completed hypothetical and experiential DD tasks involving monetary rewards, and the schizophrenia group was re-tested after four weeks. Although both groups showed qualitatively similar hyperbolic discounting functions on both tasks, they showed a quantitative DD difference. The schizophrenia showed higher DD than controls on the experiential task but normal DD on the hypothetical task. This pattern was not attributable to a range of potential confounds, including smoking status, substance use disorder status, or neurocognition. It was also not attributable to differences in the test-retest reliability, which was good for both tasks. The schizophrenia group’s robust pattern of altered experiential but normal hypothetical task performance points to key factors that may contribute to impaired DD in this disorder. These may include increased valuation of small (but not large) monetary rewards, or a hyper-sensitivity to costs associated with waiting inactively for those rewards.